Assessment of online course components from a student perspective - Katiuzka Flores Guerrero; María Cristina López de la Madrid; María Alicia Rodríguez Hernández (Universidad Autónoma de Baja California, 2016)
Various studies exist which propose assessment models for online courses from the students' perspective. However, despite displaying statistically significant links, these studies have a weakness: they assume that their components are equally important. This research was performed in light of this situation and aims to show that the importance of each component is significantly different, and identify which components are most important for students. The data collection technique used was a survey conducted on a random sample of 327 students. The Friedman test and, post hoc, the Nemenyi test were used in order to contrast the difference between variables. The main results confirm the need to consider the importance of the components of online courses to refine existing models.